The effect of family boundary flexibility on employees’ work engagement: a study based on person-environment fit theory perspective - Yang, Dexiang; Liu, Yakun; Zhang, Huiqin; Zhang, Yuxiang (Frontiers in Psychology, 2023)
Under the impact of the era of big data and public emergency, the blurring of family-work boundaries and the increasing burden of family responsibilities will pose a great challenge to employee resilience and balance between family and work, which in turn will affect employees' engagement to work. Therefore, based on the human-environment matching theory, this study aims to explore the potential mechanism and boundary conditions of employee family boundary elastic fit on work engagement. We conduct hierarchical regression and Bootstrap analysis on 433 questionnaire data to verify the hypothesis model. The study found that employees' work engagement is significantly improved when their family boundary flexibility is matched. Family-work enrichment plays a role in mediating the impact of employees' family boundary flexibility on work engagement. The relationship between family-work enrichment and work engagement is moderated by family support. Therefore, it is important for enterprises to respect and value each employee's family boundary flexibility, establish family-friendly policies, and consider personal family boundary flexibility in employees' career development planning. This will promote the enhancement of employee resilience, enable better engagement in work, improve work efficiency, and enhance the core competitiveness of enterprises.